Empagliflozin Repurposing for Lafora Disease: A Pilot Clinical Trial and Preclinical Investigation of Novel Therapeutic Targets - Giuseppe d’Orsi; Antonella Liantonio; Paola Imbrici; Nicola Gambacorta; Giorgia Dinoi; Cosimo Damiano Altomare; DEFEAT-LD Study Group; Massimo Carella (Methods and Protocols)
Background: Lafora disease (LD) is an ultra-rare and fatal neurodegenerative disorder with limited therapeutic options. Current treatments primarily address symptoms, with modest efficacy in halting disease progression, thus highlighting the urgent need for novel therapeutic approaches. Gene therapy, antisense oligonucleotides, and recombinant enzymes have recently been, and still are, under investigation. Drug repurposing may offer a promising approach to identify new, possibly effective, therapies. Methods: This study aims to investigate the conditions for repurposing empagliflozin, an SGLT2 (sodium/glucose cotransporter-2) inhibitor, as a potential treatment for LD and to establish a clinical protocol. Clinical phase: This 12-month prospective observational study will assess the safety and clinical efficacy of empagliflozin in two patients with early to intermediate LD stage. The primary endpoints will include changes in the severity of epilepsy and cognitive function, while the secondary endpoints will assess motor function, global function, and autonomy. Multiple clinical and instrumental evaluations (including MRI and PET with 18F-fluorodeoxyglucose) will be performed before and during treatment. Safety monitoring will include regular clinical assessments and reports of adverse events. Preclinical phase: In silico studies (using both molecular docking calculations and reverse ligand-based screening) and in vitro cell-based assays will allow us to investigate the effects of empagliflozin (and other gliflozins) on some key targets likely implicated in LD pathogenesis, such as GLUT1, GLUT3, glycogen synthase (hGYS), and glycogen phosphorylase (GP), as suggested in the literature and digital platforms for in silico target fishing. Results: The expected outcome of this study is twofold, i.e., (i) assessing the safety and tolerability of empagliflozin in LD patients and (ii) gathering preliminary data on its potential efficacy in improving clinical and neurologic features. Additionally, the in silico and in vitro studies may provide new insights into the mechanisms through which empagliflozin may exert its therapeutic effects in LD. Conclusion: The findings of this study are expected to provide evidence in support of the repurposing of empagliflozin for the treatment of LD.